The Effect of Birth weight on Child Development Prior to School Entry. Issue 3 (28th January 2020) - Hines, Caitlin T.; Padilla, Christina M.; Ryan, Rebecca M.
Abstract : The present study examines variation in the effect of birth weight on children's early cognitive and socioemotional outcomes by family socioeconomic status (SES). It is hypothesized that not only will lower birth weight children display worse cognitive and socioemotional outcomes prior to school entry, as prior research has found, but that effects will be stronger for lower‐SES children. Using data from the Early Childhood Longitudinal Study–Birth Cohort, the study compares the age 4 outcomes of twins discordant for birth weight (N 1, 400). Twin fixed‐effects models are run on the full twin sample and separately for low‐ and high‐SES children. Results support the study's hypotheses, suggesting that socioeconomic risk accentuates the effects of birth weight on early development.